Volumetric modulated arc therapy planning based on virtual monochromatic images: Effect of inaccurate CT numbers on dose distributions. (April 2019) - Ohira, Shingo; Komiyama, Riho; Karino, Tsukasa; Washio, Hayate; Ueda, Yoshihiro; Miyazaki, Masayoshi; Koizumi, Masahiko; Teshima, Teruki
Highlights: CT numbers in the low energy VMI can be inaccurate for high density materials. HU values in the VMI77keV is less affected by the scanning protocols than 120 kVp image. The effect of the inaccurate CT numbers on PTV was more prominent in AXB than AAA. Maximum dosimetric error in VMAT planning based on the VMI50keV was 0.5 Gy. The dosimetric error due to the inaccurate HU estimation may be clinically insignificant. Abstract: Purpose: Though virtual monochromatic images (VMIs) at low energy levels can improve image quality, the measured Hounsfield unit (HU) values can be inaccurate. We assessed the dosimetric error due to inaccurate HU estimation in volumetric modulated arc therapy (VMAT) planning. Methods: Based on the VMIs at 50 keV (VMI50keV ), 77 keV (VMI77keV ) and single-energy CT (SECT) image for a phantom with different sizes, lookup tables (LUTL and LUTS ) were created. Using an anthropomorphic phantom (head and spine regions), VMAT plans were generated based on VMI50keV, VMI77keV and SECT using the corresponding LUTL, and then, the doses were re-calculated using LUTS . For clinical cases, 30 VMAT plans (prostate, brain, and spine cases) were generated based on VMI50keV and VMI77keV . Results: In the anthropomorphic phantom study, the difference in the dosimetric parameters for planning target volume (PTV) in the VMAT plan based on the VMI77keV was smallest (within 0.1 Gy) among three types of treatment planning approach. In clinical cases, in general, the differences of the 3-dimensional gamma passing rate and dosimetric parameters in the treatment plans based on the VMI50keV were larger than those in the VMI77keV . Especially for brain cases, the difference for PTV was more prominent when AXB was used (the maximum difference was 0.5 Gy) than AAA. Conclusions: The dosimetric error due to the inaccurate HU estimation was larger in the VMIs at low energy levels. This may be clinically insignificant, but should be avoided in the VMAT treatment planning.